IDENTIFICATION AND MITIGATION OF DISORDERS IN GLOBAL SUPPLY CHAIN CHAINS (Heritage, 2022)
Organizations face a number of decisions in designing their supply chains, which include the number, type and location of production facilities, distribution centers, retail facilities, service or technical support centers, supplier selection, supply chain information management and integration of all parts. into an efficient and effective system. Improper supply chain design can undermine an organization's strategy, lead to lower revenues, less competitiveness, market share and profits. As product lines and markets change or expand, the design or redesign of supply chains becomes an even more critical issue. The risks to which supply chains are exposed are different, and their functioning can be disrupted by a number of situations, which have had serious global consequences in the past. In addition to wars, nuclear accidents, cataclysmic earthquakes, volcanic eruptions, explosions, fires and tsunamis, epidemics of SARS, MERS, HIV, Ebola and Zika viruses, as well as the latest Covid-19 pandemic, have led to the knowledge that humanity is powerless in the face of such catastrophes. Regardless of the achievements in science, extensive and long-term medical research, epidemics (pandemics) have taken millions of lives and had negative effects on society as a whole, but also on the efficiency of business and supply chains. Past epidemics have attracted the attention of scientists and industry experts, resulting in the need to reengineer organizations and adjust supply chains to future challenges. In the context of the current pandemic, serious disturbances have been reported, so a large number of industries have had unprecedented consequences. Responses to such epidemics suggest that global supply chains need to be more integrated and digitally ready. Digitization of supply chains could improve the quality of responses to epidemic-related disorders by increasing their flexibility in such circumstances. This paper identifies the most important disruptions and measures to mitigate the consequences of these disruptions in global supply chains, as well as risk management in conditions of uncertainty.
Keywords: supply chains, logistics, pandemic, uncertainty, risk, risk management